Peran Sekolah Untuk Mendorong Partisipasi Siswa dalam Pengelolaan Sampah Melalui Program GAMES (Studi Kasus di SLB Muhammadiyah Kota Bandung) - Suharyanto H. Soro; Hendra Dermawan; Tyara Ratna Nurwulan; Bella Soni Ariani (LP. Ma'arif Janggan Magetan, 2024)
Waste management in the school environment has significant challenges, especially in creating student participation in solving environmental problems. Based on research, waste produced from human activities can be differentiated between organic and inorganic waste. Effective management involves organizational components, management and operational techniques that comply with national standards. The Healthy School Movement (GSS) program has encouraged schools to be more active in waste management, where the concept of GAMES (Garbage Collection Movement) plays an important role in increasing student participation. Through this program, students are not only invited to collect waste, but also contribute to the processing process, such as recycling plastic waste into valuable works of art. Even though there are physical limitations for some students with special needs, they still participate in this activity, a demonstration that inclusive education can create a positive impact not only on individuals but also on the surrounding environment. The results of this research show that activities that involve students physically and psychologically can strengthen their sense of responsibility towards the environment and increase awareness of the importance of good waste management in schools.